Aerobic Exercise in Physical Therapy: A Natural and Accessible Path to Holistic Health: Aerobic Exercise in Physical Therapy - Anwar, Sahreen (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
In the current world, a large number of citizens do not have time to engage themselves in exercise due to tight schedules. A set of health problems, including heart disease, diabetes, obesity, and stress, may result because of this lack of physical activity. Aerobic exercises are one of the simple and natural methods of keeping healthy. These are exercises which raise your heart rate and cause you to breathe quickly. Walking, jogging, swimming, cycling, and dancing are some of the common aerobic activities. They are often performed at indoor or outdoor venues, in groups or individually, and do not necessarily require special equipment. Aerobic exercises are also referred to as cardio exercises, as they improve the functional capacity of the heart and lungs. These activities involve the use of large muscle groups, such as the legs and arms, in a consistent and sustained manner. Aerobic exercises are practiced by individuals of all ages. Simple everyday activities can serve as effective exercise—for instance, walking to the store instead of driving, taking the stairs instead of the elevator, or gardening—all of which may serve as forms of aerobic activity. Newcomers to physical activity can begin gradually with low-impact exercises such as slow walking or mild movement-based routines, and progressively increase the duration and intensity. Aerobic exercise offers numerous health benefits, which are realized when it is performed on a regular basis. It strengthens the heart and supports improved blood circulation. It also reduces blood pressure and assists in regulating blood sugar and cholesterol levels. Aerobic activity is also effective in weight management by burning excess calories. Beyond the physical benefits, aerobic exercises positively impact mental health. Regular activity helps to reduce stress, anxiety, and symptoms of depression. It helps to sleep better and boosts the level of energy. People are more energetic, active and are more optimistic in their day to day lives. In summary, aerobic exercise is an easy, safe, and natural way of improving physical and mental health. It is all inclusive and can be modified to suit individuals of different age groups and physical capacity. Aerobic exercise, when combined with physical therapy programs, may be significant in preventing diseases, rehabilitation, and improvement of the quality of life. It is important as physical therapists and other health professionals to advise, encourage and teach people to engage in aerobic exercise as part of their daily activities. It could be a formal exercise or a walk every day, each step counts. Being physically active is among the most effective and affordable decisions that one can make to improve the long-term health and functional autonomy.